Mathematical Problem Solving Ability in Indonesia - Septian, Ari; Widodo, Sri Adi; Afifah, Ismi Nur; Nisa, Dinda Zahrotun; Putri, Neneng Pitaloka Kusumah; Tyas, Mutia Dyaning; Nisa, Rhahiliyah Hafza; Andriani, Ani (Pendidikan Matematika STKIP Kusuma Negara, 2022)
This study aims to provide knowledge and references to researchers as a basis that will be used in further research. The method used is the Systematic Literature Review (SLR), which identifies, classifies, and categorizes certain topics related to research on students' mathematical problem solving abilities in Indonesia. The data used are 33 articles that have SINTA 1 and SINTA 2 accredited criteria, such as in the journals AKSIOMA and KREANO, which were taken within the last 3 years, namely 2019 to 2021. The data are grouped into 6 discussions, namely a list of journal names, year published articles, methods used, research subjects, teaching materials used, and research results. In most articles, the most widely used research method in qualitative research methods, and the research subject is 8th grade of junior high school. It was also found that 10th grade of senior high school, 11th grade of senior high school, and 10th grade of vocational high school were also research subjects. While the material in the research is mostly found about constructing flat side spaces.